Spotlight on itolizumab in the treatment of psoriasis – current perspectives from India - Budamakuntla L; Shree-Lakshmi HV; Bansal A; Venkatarayaraju SK (Dove Medical Press, 2019)
Leelavathy Budamakuntla,1 HV Shree-Lakshmi,1 Akshi Bansal,1 Shankar Kumar Venkatarayaraju2 1Department of Dermatology, Venerology and Leprosy, Bangalore Medical College and Research Institute, Bengaluru, Karnataka 560002, India; 2Department of Endocrinology, MS Diabetes Centre, Indiranagar, Bangalore 560038, India Abstract: Psoriasis is a chronic, debilitating, immune-mediated, systemic inflammatory disease affecting mainly skin, nails, and joints. Several therapeutic modalities are available depending on the severity of the disease. Long-term use of these drugs results in unwanted effects and toxicities. Recently, itolizumab, a humanized monoclonal immunoglobulin G1 antibody to CD6, has shown appreciable clinical effects and safety profile in patients with moderate-to-severe chronic plaque psoriasis. A literature search was conducted using the keywords “anti-CD6”, “psoriasis”, “phase trials”, “case series”, and “case reports”. The data from all studies conducted in India on efficacy of itolizumab in psoriasis and published before September 2017 were collected. This article provides an overview of the clinical data obtained in these published articles. Itolizumab has immunomodulatory and anti-inflammatory effects. It is efficacious and provides a good duration of remission, and hence represents a new biological agent that could be added to the therapeutic armamentarium of psoriasis. Keywords: psoriasis, biologic, monoclonal antibody, anti-CD6, Humanised IgG1 monoclonal antibody, anti CD6